Effect of metal ion etching on the tribological, mechanical and microstructural properties of TiN-coated D2 tool steel using cae PVD technique - Ali, Mubarak; Hamzah, Esah; Mohd Toff, Mohd Radzi (World Scientific, 2006)
A study has been made on TiN coatings deposited on D2 tool steel substrates by using commercially available cathodic arc evaporation, physical vapor deposition technique. The goal of this work is to determine the usefulness of TiN coatings in order to improve the micro-Vickers hardness, coefficient of friction and surface roughness of TiN coating deposited on tool steel, which is vastly use in tool industry for various applications. A pin-on-disc test was carried out to study the coefficient of friction versus sliding distance of TiN coating at various ion etching rates. The tribo-test showed that the minimum value recorded for friction coefficient was 0.386 and 0.472 with standard deviation of 0.056 and 0.036 for the coatings deposited at zero and 16 min ion etching. The differences in friction coefficient and surface roughness was mainly associated with the macrodroplets, which was produced during etching stage. The coating deposited for 16 min metal ion etching showed the maximum hardness, i.e., about five times higher than uncoated one and 1.24 times to the coating deposited at zero ion etching. After friction test, the wear track was observed by using field emission scanning electron microscope. The coating deposited for zero ion etching showed small amounts of macrodroplets as compared to the coating deposited for 16 min ion etching. The elemental composition on the wear scar were investigated by means of energy dispersive X-ray, indicate no further TiN coating on wear track. A considerable improvement in TiN coatings was recorded as a function of various ion etching rates.